CONSCIENTIOUSNESS PERSONALITY TYPE AS A PREDICTOR OF POST PURCHASE REGRET - Liana Anisa Leo; Eka Danta Jaya Ginting (Proyeksi: Jurnal Psikologi, 2012)
The aim of this research is to investigate the level of cor r el a t ion betwe en conscientiousnesspersonality type and post purchase regret on consumer. The measurement tool that was used in thisresearch is conscientiousness personality type scale and post purchase regret scale. Conscientiousnesspersonality type scale arranged by researcher according to conscientiousness personality typecomponents proposed by John, Robins & Pervin (2008), that is order, achievement striving,dutifulness, self discipline, competence dan deliberation. Whereas post purchase regret scalearranged by researcher according to post purchase regret components which was adapted from Leedan Cotte (2009) work, that is outcome regret dan process regret. The number of respondent was101 people that collected by technique of purposive sampling. Using Kendall-Tau analyses, theresult of this study shows that there was a significant relationship between conscientiousnesspersonality type and post purchase regret. Conscientiousness personality could decreased postConscientiousness Personality Type, Post Purchase Regret.purchase regret.